Nasionalisme KH. As’ad Syamsul Arifin dalam Novel Kesatria Kuda Putih Karya Ahmad Sufiatur Rahman - Khumairotul Umami (JSI: Jurnal Sejarah Islam, 2022)
The purpose of this study was to determine the role of nationalism of Kiai As'ad in the novel Kesatria Kuda Putih by Ahmad Sufiatur Rahman. The theory used in this research is Abrams' mimesis theory, Hans Kohn's Nationalism theory, and Lucien Goldmann's genetic structuralism theory. This study uses a type of library research (Library Research). Primary sources in the form of the novel Kesatria Kuda Putih by Ahmad Sufiatur Rahman and other supporting sources were obtained from books, theses, research journals, and studies related to the thesis title. This study resulted in the first, based on research findings on the national spirit of the figure KH. As'ad Syamsul Arifin concluded that the national spirit carried out by Kiai As'ad could be seen from the strategy he developed with the pioneers, the majority of whom were from the bromocorah, to face the Dutch. This attitude appears as a form of national spirit towards the nation. Second, based on the findings of the research regarding the realization of the self-sacrificing attitude of the figure KH. As'ad Syamsul Arifin, it can be concluded that Kiai As'ad was willing to sacrifice for his nation’s interests by leading directly to seize weapons belonging to the Dutch. Kiai As'ad and residents are willing to provide clothing and food for the fighters. Kiai As'ad rejected President Soekarno's offer to become Minister of Religion because of Kiai As'ad's sincerity in fighting for the homeland. He is also willing to get slandered by officials whose positions do not want to be shifted just to defend the homeland. Third, based on the research findings on the embodiment of love for the homeland from KH. As'ad Syamsul Arifin, it can be concluded that Kiai As'ad guerrillas took weapons belonging to the Dutch. The struggle is solely to defend and uphold the state.